Analisis Kedwibahasaan Anak Usia Dini Kampung Hegarmanah Desa Cibiuk Kabupaten Cianjur - Septiana, Yerika (Orasi: Jurnal Ilmu Politik dan Sosial, 2024)
The study entitled "Analysis of Early Childhood Bilingualism in Hegarmanah Village, Cibiuk Village, Cianjur Regency is a study that focuses on how bilingualism exists in early childhood. The bilingualism studied is Sundanese and Indonesian. This study aims to obtain information about bilingualism influenced by the environment. In addition, to determine the factors that influence early childhood to be faster or slower in mastering two languages. This study uses a descriptive qualitative research method with interview techniques. Based on the research that has been conducted, the researcher can find out the results, namely the Sundanese and Indonesian language skills of the children of Hegarmanah Village are still basic or still in the stage of receiving various vocabularies in the two languages. The abilities of each child are different, some are very proficient in using Sundanese, some are balanced and some are more proficient in using Indonesian. This is because of various influences, both from the playing environment and the role of parents. It can be concluded from this study, namely the first language mastered by children in Hegarmanah Village is Sundanese. There are also those whose first language is Indonesian, but overall, based on the data, most children in Hegarmanah village use Sundanese as their first language. Although their first language is Sundanese, children in Hegarmanah village can use Indonesian, with the results being 1) More able to use Sundanese, 2) Balanced language skills, and 3) More able to use Indonesian. The environment in which a child is located also greatly influences the development of a child's language.